Screening of stabilizers for LC–MS/MS analysis of clevidipine and its primary metabolite in dog whole blood. (July 2015) - Cao, Peng; Li, Gao; Huang, Ling; Zhao, Shouwei; Hu, Yang; Qin, Lixia; Qiu, Lihui; Zhu, Wenwen; Si, Luqin; Huang, Jiangeng
Background: Clevidipine is an ester-containing antihypertensive agent that undergoes rapid hydrolysis in blood. A reliable stabilizer cocktail containing citric acid and ascorbic acid was established and the LC–MS/MS method was validated for simultaneous determination of clevidipine and its major metabolite in beagle dog whole blood.Results: The stabilizer could nearly completely inhibit the esterase activity. Both analytes were extracted from whole blood by toluene and detected by MS/MS in positive ESI mode. The linearity range was 0.1–100.0 ng/ml for clevidipine and 1.0–1000.0 ng/ml for the primary metabolite.Conclusion: The stabilizer cocktail was able to effectively suppress the activity of esterase in blood. The method was successfully applied to a PK study of clevidipine in beagle dogs.